Tariff between the United States and the Philippine Islands. Certain memoranda relating to the Tariff between the United States and the Philippine Islands. January 21. 1902 - United States. Bureau of insular affair ([Washington Government Printing Office, 1902)
Just one month after the date of the above order, Manila surrendered to the American forces and the Spanish dominions on the Orient passed to American control. Manila was opened to commerce as a port of entry on August 20, 1898, in obedience to instructions from the President, and Iloilo was opened February 22,1899; Ccbu, March 14,1899; Zamboanga, Siassi, and Jolo, on December 26,1899. These are the only ports of entry in the Philippine Islands, and as they constitute convenient centers from which imported merchandise can be distributed throughout the archipelago through the medium of the coasting trade, it is not anticipated that any increase on their number will be necessary.--Excerpt from the book.
Electronic reproduction.
Keywords: Tariff -- Philippines